Rare Type Cranial Postauricular Pilonidal Sinus: A Case Report and Brief Review of Literature - Sebahattin Destek; Vahit Onur Gul; Serkan Ahioglu (Case Reports in Surgery)
A pilonidal sinus is a chronic inflammatory process, the etiology of which is still not fully elucidated. It frequently presents at the sacrococcygeal region (typical) and rarely at extrasacrococcygeal (atypical) locations, including the interdigital, axillary, inguinal, and umbilical regions, as well as the neck, face, and scalp. A 46-year-old man presented with a thirty-year history of a slowly growing nodule on the postauricular area of the scalp. The lesion was excised and diagnosed as a pilonidal sinus based on the clinical and histological findings. The purpose of this review is to report the unusual occurrence of a pilonidal sinus on the scalp and to review the literature regarding this particular location of occurrence.